Evaluation of User Satisfaction with the Health Screening Feature on Mobile JKN in Cirebon City through End User Computing Satisfaction (EUCS) - Fitri Anggraeni; Bambang Karmanto; Maula Ismail Mohammad; Lina Khasanah (Journal of Community Health Provision, 2026)
This research is motivated by the increasing role of digital health applications in supporting early disease detection, particularly through the Health Screening feature on Mobile JKN, while studies related to user satisfaction with this feature are still limited. This study aims to evaluate user satisfaction based on the End User Computing Satisfaction model. The study used a quantitative analytical descriptive design with a cross-sectional approach. The population was Mobile JKN users in Cirebon City who had used the screening feature, with a sample of 385 respondents selected using a non-probability quota sampling technique. Data were collected using a valid and reliable Likert scale questionnaire via Google Form, then analyzed univariately and bivariately using the Spearman Rank correlation test because the data were not normally distributed. The results showed that all EUCS dimensions had a strong and significant positive relationship with user satisfaction, with the Content variable being the most dominant. The conclusion suggests that improving content quality, information accuracy, display format, ease of use, and system timeliness is crucial to maintaining and increasing user satisfaction with the Health Screening feature on the Mobile JKN application.